The Process of Educating Children and Young People in the Association of Catholic Scouting "Zawisza" Federation of European Scouting - Jerzy Danecki (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Upbringing is an indispensable element of the growing up of children and youth. In the first years of life, it is the parents who exert the greatest influence on the child, trying to show the child what is right and what is wrong. Over time, when the child grows up, the parents are no longer alone in this difficult process, because they are helped by the school, the community of the Church and various associations to which children and young people can belong. This association includes the Association of Catholic Scouting "Zawisza" Federation of European Scouting. It is an association that follows a decades-old scouting tradition and is a movement based on the principles of the Roman Catholic religion.